Tangent delta low voltage high frequency ac method to measure HV underground XLPE cables - Avinash A.R.; Chakrabarty C.K.; Permal N.; Agileswari (Asian Research Publishing Network, 2023)
The Tangent Delta utilizing Low Voltage High Frequency Alternating Current is a method to test cables insulation durability. Phase shifts between the current and voltage across the cable are utilized to obtain the Tangent delta measurement. Advantages of this method compared to the market equipments are that the experimental setup is shrunk and special resolutions are improved. This method can measure as short as 1 meter HV cable's. This method was calibrated using cables manufactured with imperfections to distinguish various severities and also with a good cable as benchmark. A calibration curve was established by correlating the HFAC tangent delta measurement system's results with a 50 Hz marketed measurement system. The HFAC method is then used to measure actual field samples taken 20 meters away from a breakdown. Failure Analysis and HFAC result corresponds with the insulation measured being aged. 2006-2016 Asian Research Publishing Network (ARPN).